Diversification of investment portfolios as an instrument used by institutional investors in the capital management process - Paweł Trippner (e-Finanse: Financial Internet Quarterly, 2011)
The paper presents the essence and ways of limiting the level of investment risk through the processes of diversifying the composition of investment portfolios. The paper shows types of deposit portfolios. The author analyzed the profitability of deposit portfolios with various share of high-risk instruments in 2005-2010 as well as the influence of the recession in 2007-2008 on the profitability of particular investment portfolios.
Keywords: G11; G23; 330; collective investor; investment portfolio; investment risk management; financial instrument; capital market